Soil carbon dynamics, carbon budget and its relationship with crop yield under different cropping systems in Vertisols of Central India - COUMAR, M VASSANDA; KUNDU, S; SAHA, J K; RAJENDIRAN, S; DOTANIYA, M L; KARTHIKEYAN, K; PATRA, A K (The Indian Journal of Agricultural Sciences, 2020)
The present study was carried out in the farmers’ field during 2014–15 in the agro-ecological sub-region 10.1, covering Sehore and Vidisha of Madhya Pradesh, India. The study was aimed to quantify the annual biomass carbon addition and carbon loss from cultivated Vertisols under different cropping systems and its impact on crop yield. The result indicates that loss of soil organic carbon (SOC) due to intensive crop cultivation was 31.03% and 46.31% as compared to pristine soils of Sehore and Vidisha district, respectively. Among the cropping systems, SOC pool values are relatively higher under legume based cropping system (soybean-wheat and soybean-chickpea) than cereal-cereal cropping system (rice-wheat). The loss of carbon from passive pools was considerably lower (15.72–23.53%) under legume based cropping system as compared to cereal based cropping system (30.20%). The C balance sheet in Sehore and Vidisha districts indicates that the annual loss of C from soil was much less than the annual input of biomass C into the soil, thereby, maintaining a positive C balance in soil to the tune of 1666 (soybean- chickpea system in Sehore) to 2008 kg C (soybean-wheat system in Vidisha) in the soil. Thus, the study concludes that legume based cropping system in Vertisol are soil carbon restorative process as compared to cereal-cereal based cropping system.